Borders Up in Smoke: Marijuana Enforcement in Nebraska After Colorado's Legalization of Medicinal Marijuana. (December 2017) - Ellison, Jared M.; Spohn, Ryan E.
With the passage of Amendments 20 (2000) and 64 (2012), Colorado legalized the medicinal and recreational use of marijuana. Nebraskan law enforcement in border counties subsequently reported increases in arrests and reductions in jail space. In response, the Nebraska state legislature passed LR-520 to study the potential increased costs incurred by criminal justice agencies in border counties. To investigate this situation, we compare trends in drug arrests and jail occupancy across three areas: border counties, those that contain Interstate 80 (I-80) as a major transportation route, and the remaining counties in the state of Nebraska from 2000 through 2013. We found that border counties, but not necessarily those along the I-80 corridor, experienced significant growth in marijuana-related arrests and jail admissions after the expansion of the medical marijuana program in Colorado. Implications for research and policy are discussed.